GAMBARAN KADAR HEMOGLOBIN LANSIA DI DUSUN DEMULIH KECAMATAN SUSUT KABUPATEN BANGLI - Sugiritama, I.W.; Arijana, I.G.K.K.; Wiryawan, I.G.N.S.; Ratnayanthi, I.G.A.D.; Linawati, N.M.; Wahyuniari, I.A.I.; Laksmi, D.A.A.S. (Buletin Udayana Mengabdi; Vol 21 No 4 (2022): Buletin Udayana Mengabdi, 2023)
According to the Indonesian Ministry of Health in 2013, the rate of anemia in Indonesia was 46.3%, of which the highest prevalence was in the elderly group. The problem of anemia in the elderly is becoming very serious as the elderly population is increasing, anemia increases morbidity and mortality. Anemia in the elderly is caused by a lack of nutrients such as protein, iron, vitamin B12, folic acid, vitamin C as well as eating habits that inhibit nutrient absorption. Eighty elderly people participated in public service activities including measuring hemoglobin (Hb) levels, followed by providing multivitamins and iron supplements, and educating them on nutrient deficiency prevention. As a result, there were 27 elderly people with anemia (33.7%), 53 people (66.3%) with normal hemoglobin levels, and the rate of anemia in women (37.5%) was higher than in men. 28.1%). These data suggest a very high prevalence of anemia in the elderly, especially in older women. Keywords: anemia, elderly, hemoglobin, iron, multivitamin,